Caminhos cruzados : itinerários de pioneiros professores do ensino superior em Sergipe (1915-1954) - Oliveira, João Paulo Gama (2015)
This thesis aims to research a group of pioneering teachers of higher education in Sergipe. More specifically, the research analyzes the paths of Felte Bezerra (1908-1990), José Bonifácio Fortes Neto (1926-2004), José Silvério Leite Fontes (1925-2005), Manoel Cabral Machado (1916-2009) and Maria Thetis Nunes (1923-2009), covering their student lives, their performance in secondary education and their acting as professors in the first undergraduate classes of the Catholic Faculty of Philosophy of Sergipe (FCFS), from 1915 to 1954. The main objective of this PhD research is to analyze the individual itineraries of a group of intellectuals from school education to secondary teaching and first steps as professors at the first teacher training institution in higher education in Sergipe, the FCFS. Due to the prospective of studying five teachers who make up a portion of the "cultural elite" of Sergipe, the theoretical and methodological foundations that underpin this study meet the concepts of intellectual, itineraries and sociability structures composed by networks and microclimates of the French author Jean-François Sirinelli, along with Maurice Halbwachs's reflections on memory and Carlo Ginzburg’s about the "clues, evidence and signs." The selected sources are multiple: interviews, speeches, reports, student’s reports, class records, minutes of meetings in schools where they worked and in the FCFS, newspapers and magazines articles, graduation albums, personal diaries, "family book", time sheets, books in which diplomas were registered, minutes books, books with the employees’ contracts, school notebooks, photographs, and especially the memories of the teachers, who were subject this study in the analysis. Thus, I defend that the pioneers of higher education teachers in Sergipe were recognized intellectuals among their contemporaries, with a reputation gained by "networks" of which their families were already part of, as well as throughout the student life, as teachers of secondary education and as members of different institutions in the city of Aracaju. Their paths had already crossed in different areas of education and work, being the FCFS another intersection for their individual itineraries of intelligentsia found in Sergipe in the mid-twentieth century. Keywords: Philosophy School. History